Simultaneous speciation of inorganic arsenic (III and V) utilizing gold-manganese oxide nanoparticles modified electrochemical sensors - Zhao, Ke (2024)
Inorganic arsenic is primarily present in two stable valence states: III and V, each exhibiting different toxicological profiles. Accurately distinguishing As(III) and As(V) is, therefore, crucial for precise risk assessment and environmental monitoring. The prevalent approach for such speciation commonly involves a combination of bulk and expensive high-performance liquid chromatography (HPLC) and inductively coupled plasma mass spectrometry (ICP-MS) instruments. In response to the demand for more streamlined and efficient techniques, several alternative methods, including voltammetry, have been explored. Despite the application of gold and manganese in the voltammetric detection of inorganic arsenic, the simultaneous measurements of As(III) and As(V) have not been solved. This study introduced a novel nanocomposite with an Au-Mn ratio of 10:1 (m/m) for modifying the surface of screen-printed carbon electrodes (SPCEs). These modified SPCEs were successfully applied in the monitoring and speciation of inorganic arsenic simultaneously by voltammetry during simulated wastewater treatment for the first time. The linear range is 0.2 to 2 mg·mL-1 (ppm) with the limits of detection (LOD) of 0.048 ppm for total arsenic and 0.07 ppm for As(III), respectively. Notably, the performance and accuracies of developed voltammetric sensors for simultaneous detection of total arsenic, As(III) and As(V) were confirmed through validation with the sophisticated HPLC coupled to triple quadrupole ICP-MS (HPLC-ICP-QQQ) method.